PENTINGNYA PENDIDIKAN KESEHATAN TENTANG PHBS TERHADAP PENCEGAHAN PENULARAN SKABIES DI PONDOK PESANTREN - Mulyani, Sri; Novitayanti, Eka (Jurnal Ilmiah Kesehatan, 2020)
Background: Scabies is a skin infection by the Sarcoptes scabiei tick that causes itching. Thedisease can spread easily from human to human, from animal to animal or from human toanimal. A high prevalence of scabies is generally found in environments with a high density ofresidents and interpersonal contacts such as prisons, orphanages and Islamic boarding schools. Purpose: Knowing the ef ect of providing health education about clean and healthy lifestyle(CHLS) on changes in hygiene and healthy living behavior in people with scabies in PondokPesantren Al Asy’ariyah Kalibeber WonosoboMethods: This research is a pre-experimental study with a pretest posttest group design bycomparing the results of observations and interviews on clean and healthy living habits ofpeople with scabies before and after being given health education about clean and healthylifestyle (CHLS).. Results and Conclusion: The results of the study were analyzed with the Wilcoxon test p value<0.05, so it can be concluded that there is a dif erence or ef ect of health education about Cleanand Healthy Lifestyle (CHLS) on Clean and Healthy Life Behavior in people with scabies.